2014
DOI: 10.1016/j.jtbi.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Who mixes with whom among men who have sex with men? Implications for modelling the HIV epidemic in southern India

Abstract: In India, the identity of men who have sex with men (MSM) is closely related to the role taken in anal sex (insertive, receptive or both), but little is known about sexual mixing between identity groups. Both role segregation (taking only the insertive or receptive role) and the extent of assortative (within-group) mixing are known to affect HIV epidemic size in other settings and populations. This study explores how different possible mixing scenarios, consistent with behavioural data collected in Bangalore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Sensitivity analyses suggest the model’s simplicity did not adversely affect the model projections. Incorporating other behavioural heterogeneities is also unlikely to have affected the model findings [38] . Future analyses considering multiple interventions, HRGs and settings will use more complex models.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analyses suggest the model’s simplicity did not adversely affect the model projections. Incorporating other behavioural heterogeneities is also unlikely to have affected the model findings [38] . Future analyses considering multiple interventions, HRGs and settings will use more complex models.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis is also somewhat limited by the lack of data about sexual mixing patterns, although previous modelling has shown that, for this setting, HIV prevalence projections are largely unaffected by the underlying mixing assumptions ( Mitchell, Foss, Prudden, et al., 2014 ). Insufficient data on other factors or inconsistent data due to different data collection methods ( Phillips et al., 2013 ) also presented a challenge, leading us to make necessary simplifying assumptions in the model to match data availability ( Garnett & Anderson, 1996 ) or having to obtain some model parameter estimates from nearby districts or state-level data.…”
Section: Discussionmentioning
confidence: 99%
“…As in our prior modelling analysis ( Mitchell, Foss, Prudden, et al., 2014 ), the size of the insertive MSM subgroup was set to balance the total number of insertive and receptive sex acts in the whole MSM/TGW population. The number of receptive sex acts reported by each subgroup were distributed among the three subgroups (as their partners) in proportion to the number of insertive acts reported by each (partner) subgroup.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of sexual networks, including density, homophily (by ethnicity, sexual behavior), concurrency and temporal structure impact the spread of infectious diseases [ 24 , 28 , 41 48 ]. Recently, assortativity by race or identity group has been explored in MSM as an explanation to differences in HIV spread in selected subpopulation [ 48 , 49 ]. Yet, substantial heterogeneity remains in HIV spread, calling for more research and data on the association of personal and network related risk factor of being infected by HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Other individual characteristics (ethnicity, drug use, type of anal intercourse) [ 60 ] have been studied to help target those at risk of being infected and who would benefit the most from PrEP. Yet, these models did not investigate the role of the sexual network structure, which is indeed a more recent endeavor in models [ 26 , 43 , 49 ].…”
Section: Discussionmentioning
confidence: 99%